Analisis Kinerja Ekonomi, Sosial, dan Lingkungan dan Strategi Pengembangan Agribisnis Hidroponik (Studi Kasus di Kota Bandung) - Akbar, Falah; Charina, Anne (Universitas Galuh, 2026)
The vegetable supply deficit in Bandung required an efficient and sustainable solution. Hydroponics was considered a promising approach. This study aimed to analyze the economic, social, and environmental performance of Bara Hidro and to formulate appropriate development strategies. A qualitative case study was applied using interviews with Global Reporting Initiative (GRI) indicators, financial ratio analysis, and strategy formulation through IFE, EFE, IE, SWOT, and QSPM matrices. The findings showed an economic performance with a Net Profit Margin of 7.9%. The social aspect was reflected in community involvement through educational activities and job creation. The environmental aspect was indicated by efficient resource utilization and waste management. The analysis identified 17 internal factors consisting of 11 strengths and 6 weaknesses, along with 12 external factors consisting of 9 opportunities and 3 threats. Strategy formulation resulted in seven alternatives, with the highest Total Attractiveness Score of 6.01049 assigned to community development and agribusiness education. Strengthening this direction was expected to sustain the business while expanding positive impacts on society and the environment.